Health education to prevent respiratory infections: Experience report (Research, Society and Development, 2021)
Objective: to describe the experience lived by the nursing resident about carrying out health education during practice at the Hospital Infection Control Service of a university hospital. Methodology: This is a descriptive, qualitative, experience report type study, which was carried out at the Julio Muller University Hospital, in Cuiabá-MT, on May 26 and 27, 2020. Results and discussions: The activities were developed with the companions of patients who were admitted to the medical and pediatric clinic, resulting in the participation of 16 people. We identified that 4 participants (25%) were male and 12 (75%) were female. The prevalence of females in care practice has also been found in other studies. It was possible to observe that of the 16 companions, 6 (37.5%) were unable to develop the dynamics, which demonstrates the importance of carrying out health education activities, which help in prevention, and in health promotion. The participants showed good adherence in the educational activity in health, participating actively, solving their doubts and indicating other issues that could be addressed in the next activities. Final considerations: Considering the importance of educational activities, we understand that this practice has been enabling a better articulation between those involved, enabling them to take an active position within their health learning process.